Facile Combustion Synthesis of Carbon-Supported Titanium Oxynitride to Catalyse Oxygen Reduction Reaction in Acidic Media. (20th November 2015) - Chisaka, Mitsuharu; Ando, Yuta; Muramoto, Hirokazu
Graphical abstract: Abstract: A facile route for synthesis of nitrogen-doped TiO2 supported on carbon black (TiO x N y –C) to catalyse oxygen reduction reaction in acidic media, was developed without forming bulky TiN. This protocol involved modification of an inexpensive "solution phase combustion" process used for production of nitrogen and fluorine codoped TiO2 photocatalysts. Fluorine-free TiO x N y particles were successfully supported on carbon by adding the carbon support to the precursor dispersion containing titanium tetrafluoride and urea with stirring at 523 K, followed by pyrolysis under N2 gas as a modification of the photocatalyst synthesis. The catalyst activity depended on the pyrolysis temperature, where the optimal activity was achieved by pyrolysis at 1073–1123 K. The active sites are proposed to be rutile TiO2 doped with nitrogen atoms containing oxygen defects. The developed synthesis route requires less than half of the time required for our previous protocol utilizing two-step pyrolysis under a mixture of H2 /O2 /N2 gas and NH3 -gas and is also significantly more economical.